Step IV of the muon ionization cooling experiment (MICE) and the multiple scattering of muons - Carlisle, T (2013)
The Muon Ionization Cooling Experiment (MICE) is the first technical demonstration of muon ionization cooling, using a prototype section of a Neutrino Factory cooling channel. MICE is currently under construction at the Rutherford-Appleton Laboratory in the UK and will make the first cooling measurements in 2015, in Step IV of the experimental programme. Cooling predictions in Monte Carlo simulations of Step IV were found to disagree with the predictions of the 'cooling formula', a widely-used approximation, by up to 30% in liquid hydrogen (LH2). This disagreement was shown to originate, largely, from the multiple scattering expression used in the cooling formula. It was necessary to go back to the fundamental physics of scattering to derive a more accurate expression that includes scattering from atomic electrons. A modified form of the cooling formula was derived using this expression and gave better agreement with the Monte Carlo in LH2. Predictions are given for the equilibrium emittance, using the new expression, for seven low Z materials at muon momenta of 140, 200 and 240 MeV/c. Theories which predict the distribution of multiple scattering angles are briefly reviewed, focusing on Moliere theory and its variants, which are the most widely-used theories. The distributions predicted by these theories are used in most Monte Carlo codes but their implementation is not transparent, especially regarding the treatment of scatters with atomic electrons, which are important in low Z materials. A simple Monte Carlo model to predict multiple scattering distributions was developed that correctly treats scatters off electrons. The model gives very good agreement with measurements by the MuScat Experiment. Investigations were made into the possibility of measuring multiple scattering in MICE Step IV, both with and without the magnetic field. Preliminary results suggest that measurements are easier with no magnetic field, where tracks are straight. Corrections to account for the resolution of the scintillating-fibre trackers are required in both cases, but these are substantially smaller when straight tracks are used.